Incidence of concomitant chondral/osteochondral lesions in acute ankle fractures and their effect on clinical outcome: a systematic review and meta-analysis - Darwich, Ali; Adam, Julia; Dally, Franz; Hetjens, Svetlana; Jawhar, Ahmed (Archives of orthopaedic and trauma surgery, 2021)
Despite successful osteosynthesis, some patients report residual symptoms after ankle fractures. One of the reasons behind the postoperative complaints might be traumatic concomitant chondral lesions (CL) and/or osteochondral lesions (OCL) within the ankle joint. The study aims to systematically review the incidence of CL and/or OCL in ankle fractures and to assess their effect on the clinical outcome.
Published: 31 October 2020
Gesehen am 22.06.2021